Money Demand and the Stock Market in a General Equilibrium Model with Variable Velocity - Boyle, Glenn W. (Journal of Political Economy, 1990)
A monetary model of asset pricing is used to explain observed correlations between money velocity and stock prices. Output stocks cause velocity and nominal stock prices to move in opposite directions but may cause velocity and deflated stock prices to move in the same direction. Although monetary shocks are neutral, changes in monetary expectations have real effects because of their impact on the expected purchasing power of money balances carried into the future. Thus changes in expected monetary growth alter expected real equity returns and inflation, and changes in monetary uncertainty alter the equity risk premium.